Cross-sectional survey on cancer patients’ concerns and consultation needs with pharmacists at the time of initial diagnosis - Tomofumi Watanabe; Atsunobu Sagara; Tomoya Abe; Masato Komuro; Koharu Yubune; Satoshi Yoshikawa; Hiroyuki Terakado (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background The immediate post-diagnosis period is a critical phase for cancer patients, marked by significant informational and emotional distress. Although pharmacists are well-positioned to provide support during this time, limited research has investigated patients’ specific concerns and consultation needs immediately after diagnosis, particularly in differentiating between hospital and community pharmacists. This study aimed to clarify cancer patients' concrete concerns and consultation preferences immediately following diagnosis, with a focus on the respective roles of hospital and community pharmacists. Methods A nationwide cross-sectional web-based survey was conducted among 1,031 adult cancer patients in Japan. Participants selected relevant concerns from a 21-item structured questionnaire across four domains: Cancer and Cancer Treatment (CCT), Cancer Pain and Palliative Care (CPPC), Medications Other Than Cancer Treatment (MOCT), and Daily Life During Cancer Treatment (DLCT). For each concern, participants indicated whether they preferred to consult hospital pharmacists, community pharmacists, or both. McNemar tests were used to compare paired proportions (P < 0.001). Results A total of 89.2% of participants reported at least one concern at diagnosis. The most frequently reported concerns were treatment-related, including side effects (49.2%), treatment costs (48.0%), psychological distress (41.6%), and mechanisms of anticancer drugs (38.8%). Patients expressed significantly stronger preferences for consulting hospital pharmacists over community pharmacists on treatment-specific topics such as side effects (34.7% vs. 13.8%), drug mechanisms (39.3% vs. 18.5%), and medications to relieve physical discomfort (36.1% vs. 17.0%) [all P < 0.001]. In contrast, MOCT-related concerns, such as drug interactions and medication management, elicited similarly high consultation preferences for both pharmacist types (> 40%). DLCT and CPPC-related concerns were associated with relatively lower consultation demands overall. Conclusions Cancer patients experience diverse and substantial informational and emotional needs immediately after diagnosis. Hospital pharmacists are particularly valued for treatment-specific support, while both hospital and community pharmacists are seen as essential resources for broader medication-related concerns. Enhancing cooperation between hospital and community pharmacists, and strengthening pharmacist-led support tailored to patients' needs at diagnosis may significantly improve patient-centered care and quality of life.